Sustainability analysis of various air-assisted orchard sprayer fan designs: Performance, energy and carbon footprint - İtmeç, Medet and Bayat, Ali and Özlüoymak, Ömer Barış and Soysal, Alper (International Journal of Agricultural and Biological Engineering, 2024)
The fan unit design of air-assisted orchard sprayers directly affects the amount of deposits on leaf surfaces, the amount of airborne drift and endodrift, as well as the fuel consumption during the operation. Therefore, in addition to reducing fuel consumption by modifying the fan inlet side, re-designing fan blade type, deflector type, and discharge side design of the turbofan unit has been a recent increasing trend in R&D studies to achieve higher airflow and better air-jet uniformity. In this study, to achieve better air penetration into the tree canopy, design and performance comparisons were made of three different turbofan designs, one of which is currently available on the market and popular in sprayers, while the other two are new designs. In accordance with EN ISO 9898, wind tunnel tests were carried out at a PTO rotation speed of 540 r/min with fan blade angles of 15º, 30º, and 45º and fan ratios of 1:3.5 (1890 r/min) and 1:4.5 (2430 r/min) for each turbofan. Simultaneously, air velocity measurements were made from the fan inlet side of the wind tunnel and from the discharge side of the fan. Furthermore, torque (N•m), speed measurement (r/min), and instantaneous fuel consumption (L/h) depending on the operation were also measured. The success of the fan blade type was determined by fan efficiency, and specific fuel consumption was an additional indicator of operating conditions. In experiments, 77.5% fan efficiency and specific fuel consumption 0.44 kg/kW•h was achieved with NVS fan. Regardless of fan type, several operational conditions available to users in fan design were statistically proven to be ineffective in terms of airflow. Keywords: air-assisted orchard sprayer, turbofan performance evaluation, energy usage in agriculture, carbon footprint DOI: 10.25165/j.ijabe.20241706.9244 Citation: İtmeç M, Bayat A, Özlüoymak Ö B, Soysal A. Sustainability analysis of various air-assisted orchard sprayer fan designs: Performance, energy and carbon footprint. Int J Agric & Biol Eng, 2024; 17(6): 32–37.